CONSEQUENCES OF THE ABRUPT TRANSITION FROM SEDENTARISM TO HEALTHY PHYSICAL HABITS AND THE IMPORTANCE OF SPECIALIZED MONITORING: AN INTEGRATIVE REVIEW (CIPEEX, 2025)
Sedentarism is a significant global problem, associated with the development of various chronic conditions, such as heart disease, type 2 diabetes, and certain types of cancer, in addition to mental health complications like depression and anxiety. The abrupt transition from a sedentary lifestyle to physical activity can result in musculoskeletal injuries and other health problems. Digital influencers, often without adequate qualifications, may promote inadequate and potentially harmful exercise practices. This study aimed to investigate the complex interaction between health, sedentarism, and physical activity, highlighting the importance of specialized monitoring. The study is an integrative bibliographic review on themes such as health, sedentarism, transition to physical activities, correlations between health and sedentarism, in addition to the consequences these habits entail for the human body and its response to physical stress. Electronic scientific articles published between 2020 and 2024, in English and Portuguese, were used from the Scientific Electronic Library Online Scielo, PubMed Unique Identifier (Pubmed), and Google Scholar databases. The obtained results indicate that specialized professionals play a fundamental role in planning and monitoring the transition to an active lifestyle, ensuring that this change occurs safely and effectively. Furthermore, regular physical activity is essential for the prevention and control of chronic diseases, improving quality of life and overall well-being. It is concluded that professional guidance is recommended to avoid injuries and maximize the benefits of physical activity, resulting in a safe and sustainable transition to a more active lifestyle.
Keywords: Habit changes; Sedentarism; Physical activities